ETIOLOGY AND PATHOGENESIS FEATURES OF INFLAMMATORY PERIODONTAL DISEASES (Review) - Zh. V. DZAMPAEVA (Кубанский научный медицинский вестник)
Aim. Conduct the analysis of modern literature on the etiology and pathogenesis of inflammatory periodontal diseases.Materials and methods. Analysis of literature in the last 5 years in E-library and PudMed systems.Results. The leading role of parodontopathogenic microflora in the emergence of periodontitis is demonstrated. The data of studies confirming that the occurrence of inflammatory periodontal diseases is caused not only by the action of the microflora of the dental plaque as the main parodontopathogen but also by a number of local and general factors reducing the resistance of the whole organism and determining the prevalence and nature of the inflammation in the periodontium.Conclusion. The etiology and pathogenesis of periodontal diseases are rather complex, diverse, and have not been fully disclosed to date. The researches in this field are conducted on the regular and the methods of diagnosis and treatment are improving.